Short review of the Twentieth-century Spanish lesbian narrative: Roles and relevance of eroticism (XXI Century. Spanish Literature and Culture, 2019)
From the beginning of the 20th century, the representation of the female homo-eroticism in the Spanish narrative has shown an interesting and unequal wide range. We will take into account texts that reflect loving relationships between women –in a hidden or in an explicit way-, as much in novels where female homosexuality is not the main topic, as in others where this is the primary issue. Paying attention to female written works, we will address the presence of eroticism in this corpus, presenting the evolution of its nature and characteristics. We will start with early novels such as Zezé (1909), by Ángeles Vicente, and continue with important examples of late 20th-century narrative in the review of implications of homo-eroticism in the character’s identity, intimacy and public and social life.
Keywords: Female eroticism; lesbianism; Spanish novel; 20th century